A Survey of Environmental Sustainability Practices in Dialysis Facilities in Australia and New Zealand. Issue 12 (December 2022) - Talbot, Benjamin; Barraclough, Katherine; Sypek, Matthew; Gois, Pedro; Arnold, Leila; McDonald, Stephen; Knight, John
Visual Abstract: Abstract : Background and objectives: Climate change is the biggest global health threat of the twenty-first century. Health care itself is a significant contributor to greenhouse gas emissions, and dialysis programs contribute disproportionately. Nephrology societies have called for increased recognition and action to minimize the environmental effect of dialysis care, but little data exist regarding environmental sustainability practices within dialysis facilities worldwide. This survey reports a baseline of environmental sustainability practices of dialysis facilities in Australia and New Zealand. Design, setting, participants, & measurements: An online survey was used to collect data regarding key areas of environmental sustainability practices within dialysis facilities between November 2019 and December 2020. An invitation to complete the survey was sent to the heads of all dialysis facilities in Australia and New Zealand. Results: Responses were received from 132 dialysis facilities, representing 33% (122 of 365) of dialysis services within Australia and New Zealand. Most responses were from public satellite facilities (53 of 132; 40%), in-center dialysis facilities (33 of 132; 25%), and co-located dialysis and home therapies facilities (28 of 132; 21%). Opportunities for improvement in environmental sustainability practices were identified in three domains. ( 1 ) Culture. A minority of facilities reported having an environmental sustainability strategy in place (44 of 132; 33%) or undertaking sustainability audits (27 of 132; 20%). Only 7% (nine of 132) reported the inclusion of environmental training in staff induction programs. ( 2 ) Building design, infrastructure, and energy use. Few facilities reported the use of renewable energy (18 of 132; 14%), reclaiming reverse osmosis reject water (16 of 126; 13%), or the use of motion-sensor light switches (58 of 131; 44%). ( 3 ) Operations. A minority of facilities reported waste management education (47 of 131; 36%), auditing waste generation (23 of 132; 17%), or that environmental sustainability was considered in procurement decisions (33 of 132; 25%). Conclusions: Environmental sustainability is not currently prioritized in clinical practice, building design and infrastructure, or management systems in Australian and New Zealand dialysis facilities responding to this survey.